Pemenuhan Hak Pendidikan pada Anak Binaan di LPKA Blitar pada Masa Pandemi COVID-19 - Mubarok, Nafi; Sulthon, M. (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
This article intended to discover and analyze the fulfillment of the educational rights of assisted children at LKPA Blitar during the COVID-19 pandemic and the obstacles to fulfilling the educational rights of assisted children at LKPA Blitar during the COVID-19 pandemic. Two significant findings can be elaborated from the research. Firstly, the educational rights of children at LPKA Class I Blitar during the Covid-19 pandemic have been fulfilled and have been implemented by LPKA Class I Blitar by existing provisions, namely Law no. 23 of 2002 concerning Child Protection, Law no. 11 of 2012 concerning the Juvenile Criminal Justice System and Law no. 20 of 2003 concerning the National Education System. Secondly, there are several obstacles in implementing education for students at LPKA Class I Blitar during the COVID-19 pandemic related to several problems. The limited educational and coaching facilities, the level of education and motivation of correctional students, and factors changing the methods used in the learning process hindered the successful fulfillment of educational rights to the children.